2021
DOI: 10.3390/agronomy11050966
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Co-Inoculation Alleviated Salt Stress in Seedlings Cucumber

Abstract: Soil salinity has become a serious threat to crop growth and productivity and has aggravated the gap between sustainable food supply and population growth. Application of plant growth-promoting rhizobacteria (PGPR) has emerged as a novel way of alleviating the harmful effects of salt stress and improving soil nutrients. The aim of this study was to study the effects of exposure cucumber seedlings at one co-inoculation of Bacillus licheniformis and B. subtilis, a mitigation of salt stress in cucumber seedlings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In addition, PCA and clustering analysis outcomes revealed the prolific effect of bioinoculants on kidney bean yield at both locations. A similar study by Qi et al (2021) also determined the best treatment through PCA and the role of plant growth promoting property attributable to plant physiological parameters through correlation analysis. Similar PCA cum clustering method was also employed by Sharma et al (2011) for determining the best Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, PCA and clustering analysis outcomes revealed the prolific effect of bioinoculants on kidney bean yield at both locations. A similar study by Qi et al (2021) also determined the best treatment through PCA and the role of plant growth promoting property attributable to plant physiological parameters through correlation analysis. Similar PCA cum clustering method was also employed by Sharma et al (2011) for determining the best Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, PGPRs are an important functional component of biofertilizers in laboratory research and agricultural production (Vessey, 2003;Salme et al, 2017). Numerous studies have indicated the promotion mechanisms of PGPR, including increasing the activity of antioxidant enzymes and metabolite accumulation and regulating the content of plant endogenous hormones (Panwar et al, 2016;Qi et al, 2021). Apart from this, most of the phosphorus is present in solid form in the soil, which is difficult to be harnessed by plants; however, previous studies have reported that PGPR improve the plant uptake of mineral elements, especially phosphorus (Dilfuza et al, 2017;Cordero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, further tolerance tests were carried out using 10% NaCl, and the growth was reduced compared to the 5%, yet most of the bacterial isolates were capable of growing and only two stains had weak growth (SALIR5) and (SOVERR2). According to the literature, numerous bacteria including B. subtilis could promote plant growth under both normal and salt-stress conditions 93 , 94 . Furthermore, when salinity stress is increased, plants increase the synthesis of ethylene to decrease their growth, this is done by the production of 1-aminocyclopropane-1-carboxylic acid (ACC).…”
Section: Resultsmentioning
confidence: 99%